PATRONAGE POLITICS AND CLIENTELISM IN HOUSING WELFARE: THE CASE OF GAWAD KALINGA (GK) VILLAGES IN PARAñAQUE CITY, THE PHILIPPINES - VILLANUEVA, PRINCE AIAN G; SALAZAR, JESSA NICOLE P. (Universitas Muhammadiyah Yogyakarta, 2015)
Patronage politics has become a defining charac-teristic of the Philippine political landscape. Clientelism, a form of patronage, is often studied as disadvantageous in governance and democratic consolidation. While the patron-client framework remains the most influential among schools of thought that explain Philippine politics, transforma-tions in a clientelist exchange are evident given changes in political, cultural and economic settings. Using this frame of new clientelism, we look at and revisit the structure of patronage in the provision of housing welfare in the Philippines, focusing now on the roles of three important actors? the nongov-ernmental organization, the state through the local government and the recipients or beneficiaries? in an urban setting, thus deviating from the traditional conception of patronage and clientelist politics. This relationship of clientelist exchange is presented in our Accomplice-Principal-Accessory (APA) model ofclientelism, with the local government unit of Parañaque City as accomplice, the Gawad Kalinga (GK) as the principal agent, and the recipients or beneficiaries as accessories in the provision of hous-ing welfare.